Hemorrhagic Transformation in Cardioembolic Stroke with Anticoagulant Use: A Case Report - Tasrif, Ari Bandana (Science: Indonesian Journal of Science, 2026)
Embolic stroke is a subtype of ischemic stroke characterized by the sudden onset of severe neurological deficits due to abrupt vascular occlusion. One of its important complications is hemorrhagic transformation (HT), defined as bleeding within infarcted brain tissue. This case report describes a 49-year-old male with a history of prior stroke and warfarin use who presented with decreased consciousness. Brain CT scan revealed extensive cerebral infarction with hemorrhagic transformation classified as HI-1 based on the European Cooperative Acute Stroke Study (ECASS) criteria. HT results from a complex interplay between blood–brain barrier disruption, reperfusion injury, and risk factors such as large infarct size and anticoagulant use. Management includes hemodynamic stabilization, discontinuation and reversal of anticoagulation, and intracranial pressure control. Although HI-1 is considered less severe than parenchymal hematoma, it still carries significant clinical implications, particularly when associated with cerebral edema. Early detection and appropriate management are essential to improve patient outcomes.